Profile of Science Literacy Skill Domain Knowledge of SMPN 2 Bua Ponrang - Yanti, Rosmalah; Prihatin, Titi; Khumaedi, Khumaedi (Journal of Primary Education, 2018)
The assumptions of the intelligent category of students in society are still based on the assessment of knowledge despite authentic assessment. This study aims to describe the science literacy ability of grade VII students of SMPN 2 Bua Ponrang in the knowledge domain consisting of procedural knowledge, epistemic knowledge, and content knowledge. The research method used descriptive quantitative. The sample is determined by using simple random sampling with the number of sample counted 31person. The results showed procedural knowledge of 37, 34%, epistemic knowledge of 34,91% and content knowledge of 27,94%. Maximum score obtained is 55, an average value of 39.77 and a minimum score of 20. It can be concluded improve the ability of science literacy, especially in the domain of knowledge. This research is hoped to give thought contribution in solving science literacy problem so that it can inspire to design activities and factors that can improve science literacy ability.